Biomarkers in acute myocardial infarction: current perspectives - Aydin, Suleyman; Ugur, Kader; Aydin, Suna; Sahin, Ibrahim; Yardim, Meltem (Dove Medical Press Ltd, 2019)
Purpose: Acute myocardial infarction (AMI) is the most common cause of death in the world. Comprehensive risk assessment of patients presenting with chest pain and eliminating undesirable results should decrease morbidity and mortality rates, increase the quality of life of patients, and decrease health expenditure in many countries. In this study, the advantages and disadvantages of the enzymatic and nonenzymatic biomarkers used in the diagnosis of patients with AMI are given in historical sequence, and some candidate biomarkers - hFABP, GPBB, S100, PAPP-A, RP, TNF, IL6, IL18, CD40 ligand, MPO, MMP9, cell-adhesion molecules, oxidized LDL, glutathione, homocysteine, fibrinogen, and D-dimer procalcitonin - with a possible role in the diagnosis of AMI are discussed. Methods: The present study was carried out using meta-analyses, reviews of clinical trials, evidence-based medicine, and guidelines indexed in PubMed and Web of Science. Results: These numerous AMI biomarkers guide clinical applications (diagnostic methods, risk stratification, and treatment). Today, however, TnI remains the gold standard for the diagnosis of AMI. Details in the text will be given of many biomarkers for the diagnosis of AMI. Conclusion: We evaluated the advantages and disadvantages of routine enzymatic and nonenzymatic biomarkers and the literature evidence of other candidate biomarkers in the diagnosis of AMI, and discuss challenges and constraints that limit translational use from bench to bedside.
Keywords: acute myocardial infarction; cardiac protein; cardiac peptide